2020
DOI: 10.13189/saj.2020.080710
|View full text |Cite
|
Sign up to set email alerts
|

Jakarta Athletics Training during the COVID-19

Abstract: In 2019, all countries experience the corona virus including Indonesia. The spread of the Covid-19 virus outbreak caused obstacles in the athletics training process. This study used a Google form help questionnaire by asking 10 questions to 104 Elite athletes respondents in DKI Jakarta. The results showed 100% were athletes in DKI, as many as 65.4% stated that athletes experienced co-19 effects. As many as 73.1% said exercise could still be done during the outbreak, 76.9% of athletes stated that the training p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…For example, as many as 60 students become the sample in the study [9]. The next study [10] was conducted by a survey on a study sample of 104 elite athletes respondents in Jakarta. In the article [30], it was 84 respondents only.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, as many as 60 students become the sample in the study [9]. The next study [10] was conducted by a survey on a study sample of 104 elite athletes respondents in Jakarta. In the article [30], it was 84 respondents only.…”
Section: Discussionmentioning
confidence: 99%
“…64,4% of respondents stated online exercises made the training process easier, and 35,6% of participants said there were no obstacles. The results of the study [10] found out that online training is suitable for athletes to care athletes' health.…”
Section: Literature Reviewmentioning
confidence: 94%
See 3 more Smart Citations